2011
DOI: 10.1029/2011gl049801
|View full text |Cite
|
Sign up to set email alerts
|

Observation of decadal change in the Atlantic meridional overturning circulation using 10 years of continuous transport data

Abstract: The meridional overturning circulation (MOC) represents the main mechanism for the oceanic northward heat transport in the Atlantic, and fluctuations of this circulation are believed to have major impacts on northern hemisphere climate. While numerical ocean and climate models and paleo‐records show large variability in this circulation, the use of direct observations of the MOC for detecting climate‐timescale changes has proven difficult so far. This report presents the first observational record of MOC measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 23 publications
10
103
4
Order By: Relevance
“…10b). This structure is consistent with the vertical structure of the NADW transport observed in the western basin by MOVE at 16 • N (Send et al, 2011). Send et al (2011) showed that the annual mean NADW transport has two southward maxima located at 2000 and 4000 m, corresponding to the LSW and DSOW, respectively, and a minimum in between centered at 3000 m, corresponding to the ISOW.…”
Section: Horizontal Circulation Patternsupporting
confidence: 72%
See 4 more Smart Citations
“…10b). This structure is consistent with the vertical structure of the NADW transport observed in the western basin by MOVE at 16 • N (Send et al, 2011). Send et al (2011) showed that the annual mean NADW transport has two southward maxima located at 2000 and 4000 m, corresponding to the LSW and DSOW, respectively, and a minimum in between centered at 3000 m, corresponding to the ISOW.…”
Section: Horizontal Circulation Patternsupporting
confidence: 72%
“…This structure is consistent with the vertical structure of the NADW transport observed in the western basin by MOVE at 16 • N (Send et al, 2011). Send et al (2011) showed that the annual mean NADW transport has two southward maxima located at 2000 and 4000 m, corresponding to the LSW and DSOW, respectively, and a minimum in between centered at 3000 m, corresponding to the ISOW. The high oxygen concentration in this area also implies the presence of relatively recently formed waters of northern origin (LSW, ISOW, and DSOW), which is also evident from higher transient tracer concentrations (e.g., chlorofluorocarbon, CFC; Molinari et al, 1992).…”
Section: Horizontal Circulation Patternsupporting
confidence: 72%
See 3 more Smart Citations